2021
DOI: 10.1002/cdq.12279
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing COVID‐19‐Related Career Concerns Using Bioecological Systems: Implications for Career Practice

Abstract: The COVID‐19 pandemic has affected many aspects of the global society, including the workforce, with many effects yet to be seen. Career professionals in various settings are positioned to support clients and students through pandemic‐related career concerns. Bronfenbrenner's (1979, 2001, 2005) bioecological systems model provides a framework that can aid in conceptualizing clients' and students' presenting issues within the complex nature of their environments. In this theoretical article, we contextualize CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
2
0
3
Order By: Relevance
“… Rothengatter et al (2021) , however, concluded that the trimmed confidence of passengers would cause difficulties in returning to the pre-pandemic expected growth for mass transportation modes. Per the ongoing development of the pandemic and the abrupt disruption to the industry, most companies find it hard to maintain their operations status quo ( Belser and Prescod, 2021 ). After the pandemic had lasted for three-fourths of a year, Cathay Dragon shut down due to its financial incapability ( Lee, 2020 ).…”
Section: Research Backgroundmentioning
confidence: 99%
“… Rothengatter et al (2021) , however, concluded that the trimmed confidence of passengers would cause difficulties in returning to the pre-pandemic expected growth for mass transportation modes. Per the ongoing development of the pandemic and the abrupt disruption to the industry, most companies find it hard to maintain their operations status quo ( Belser and Prescod, 2021 ). After the pandemic had lasted for three-fourths of a year, Cathay Dragon shut down due to its financial incapability ( Lee, 2020 ).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Enhanced government policies, developed using this theory, would provide the foundation for future scholars to examine strategies, which could be used to improve the cultural and creative sector’s development potential. Using the theoretical foundation for developing government policies could work for social welfare as “individuals are influenced indirectly by systems of which they are not directly members” (Belser and Prescod, 2021, p. 359). This is particularly important as desired economic development is yet to be achieved from the policy agenda, which has been pursued by the developing economies over the past two decades (Abisuga Oyekunle and Sirayi, 2018).…”
Section: Discussion and Theory Developmentmentioning
confidence: 99%
“…A Qualitative Investigation of Perceived Stress in the COVID-19 Pandemic Begüm SERİM-YILDIZ 1 , S. Burcu ÖZGÜLÜK ÜÇOK 2 , Çiğdem TOPÇU-UZER 3 , Claudia CHIAROLANZA 4 , Ashley K. RANDALL 5 ÖZ 2019 yılında Çin'de ilk koronavirüs vakasının görülmesinin ardından farklı ülkelerden vaka bildirimleri gelmiş ve bunun üzerine 2020 yılında Dünya Sağlık Örgütü pandemi ilan etmiştir. Bu süreçte sokağa çıkma yasağı, online çalışma, uzaktan eğitim gibi önlemler alınmış ve bu önlemlere ilişkin, kişilerin günlük yaşam alışkanlıkları ve birbirleriyle etkileşim kurma ve sürdürme şekilleri değişmiştir.…”
Section: Covid-19 Pandemisinde Algılanan Stres üZerine Nitel Bir çAlışmaunclassified
“…öğelerinin de etkisiyle farklılaştığı söylenebilir. Bunların yanı sıra ekolojik sistem modeline sonradan dahil edilen kronosistem katmanının zaman içinde gerçekleşen olay örüntülerine karşılık geldiği düşünülerek, bireylerin kriz tepkilerinin dahil oldukları nesil etkisiyle de farklılaştığını gözlemlemek mümkündür 4 .…”
Section: Introductionunclassified